Quantifying Feeding Regimes on Weaned Sows Under Tropical Papua Pig Keeping Systems - Iyai, DA; Saragih, D; Kayadoe, M (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2013)
Body weight measurement of weaned sow using several feeding regimes was done under traditional pig keeping systems in West Papua, Indonesia. Feeding quantification using local and non-conventional feeds applied by pig farmers were rationed. Feeds used were 1, 2 and 3 kg in fresh basis. Energy contents of each ration were 34.73, 32.63 and 36.39 MJ kg DM, respectively and protein rations were of 0.62, 0.34 and 0.99 kg CP DM. Initial sowâs body weight was in the average of 87 kg. The second feeding regimes with 2 kg day-1 on offer, obtained ransom with quality of balance, energy rich and protein rich, i.e. 22.69, 21.99 and 24.92 MJ kg DM, respectively and protein in ransom of 0.35, 0.26 and 0.72 kg CP DM. Feeding regimes with 1 kg day-1 on offer, we obtain ration with quality of balance, energy rich and protein rich, i.e. 12.04, 11.34 and 12.46 MJ kg DM, respectively and protein in ransom with 0.27, 0.18 and 0.36 kg CP DM. Initial weaned body weight was 87 kg. Â A simulation using one factorial of feeding regimes was established, which was drawn and simulated using Simile version 4.7 and no environmental factors were incorporated in this model simulation. The results of this study showed the increasing body weight of sows was detected by using 3 kg of feed daily in 14 days after weaning. While 2 kg feed day-1 only met the maintenance requirement. Therefore, Â there were no meat or fat deposition. Feed of 1 kg per day could induce negative impact in starvation and Â body weight lost. Insufficient feed intake can induce negative impact on physiological mechanism of the sows. This is at risk while weaned sow would enter mating season and gestation period. Feeding regimes with more that 3 kg and energy ration of 34.73 MJ kg DM and digestibility of 0.82 resulted in a positive effect on sow body weight gain.Â Animal Production 15(2):106-118, May 2013